Prediction of intent to be active physically through the theory of self-determination - Carrón, Maria (2019)
The main objective of this study is to know motivational variables and healthy lifestyles which predict the intention to be physically active, using the Self-Determination Theory (Deci & Ryan, 1985). Several authors (Fernández-Ozcorta, Almagro, & Saenz-López, 2015) showed students who have satisfied their basic psychological needs (BPN) and more self-determined motivation will have a greater intention to remain physically assets in the future. The sample consisted of 187 Spanish students in physical education classes (87 boys and 100 girls), belonging to three schools of Secondary Education of Badajoz, aged between 13 and 23 years, average age 15.5 years (SD = 1.70). We used perceived Locus Scale Causality in Physical Education (PLOC Scale), Scale measuring basic psychological needs (BPNES), Questionnaire Healthy Lifestyles (EVS), and scale of measurement of intentionality to be physically active (MIFA). We used analysis of reliability or internal consistency of the items and a regression analysis using the method of introducing block.